ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN IPAS DI SEKOLAH DASAR KELAS V SDN 2 BATUR - Diatmika, I Putu; Sudirman, I Nyoman (Jurnal Pendidikan DEIKSIS, 2025)
Abstract Research with the title Critical Thinking Ability of Class V Students in Social Science Learning at SD 2 BATUR. (Magdalena et al., 2021) This research aims to: Determine the critical thinking abilities of fifth grade students in learning science and science, identify factors that influence students' critical thinking abilities. and factors that influence the critical thinking abilities of class V students in science and science learning at SDN 2. This research will use a qualitative descriptive method. The subjects of this research are fifth grade students at SD 2 BATUR who are divided into three categories: High critical thinking ability, (Ilham & Hardiyanti, 2020) Medium critical thinking ability, Low critical thinking ability. Apart from these 3 categories, this research also uses Data collection techniques include observation, tests and interviews. The results of the research are 3 categories, including students with high critical thinking ability categories who can fulfill all critical thinking indicators. Students with moderate critical thinking ability categories are able to meet three indicators. Students with low critical thinking ability categories are only able to meet two indicators. This is also due to several factors that influence students' critical thinking ability, namely as follows: internal factors such as physical condition, anxiety, motivation, interaction and intellectual development and external factors related to outside individual in the form of a social environment.